2013
DOI: 10.1093/nar/gkt1037
|View full text |Cite
|
Sign up to set email alerts
|

Topoisomerase II minimizes DNA entanglements by proofreading DNA topology after DNA strand passage

Abstract: By transporting one DNA double helix (T-segment) through a double-strand break in another (G-segment), topoisomerase II reduces fractions of DNA catenanes, knots and supercoils to below equilibrium values. How DNA segments are selected to simplify the equilibrium DNA topology is enigmatic, and the biological relevance of this activity is unclear. Here we examined the transit of the T-segment across the three gates of topoisomerase II (entry N-gate, DNA-gate and exit C-gate). Our experimental results uncovered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 45 publications
4
25
0
Order By: Relevance
“…Indeed our attempts to construct such mutants in E. coli topo IV have resulted in enzymes with little or no activity. Notwithstanding this, the data in this paper, and previously published work8131921, strongly support the idea that the DNA exit gate is an important determinant of topology simplification by type IIA topoisomerases.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Indeed our attempts to construct such mutants in E. coli topo IV have resulted in enzymes with little or no activity. Notwithstanding this, the data in this paper, and previously published work8131921, strongly support the idea that the DNA exit gate is an important determinant of topology simplification by type IIA topoisomerases.…”
Section: Discussionsupporting
confidence: 86%
“…We can envisage that its presence in type IIA enzymes might inhibit reverse strand passage having the effect of skewing the distribution of the products of relaxation, catenation/decatenation and knotting/unknotting reactions. Recent experiments21 support the notion of ‘backtracking' of the T segment in topo II enzymes, a concept originally described as ‘on-enzyme equilibrium' with DNA gyrase48. Construction of a yeast topo II mutant with an exit-gate deletion generates an enzyme unable to carry out topology simplification21, strongly supporting the idea that topology simplification is dependent on exit-gate integrity.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Structural studies and direct mechanical measurements have revealed that Topo IIA bend DNA upon binding (Dong and Berger 2007;Hardin et al 2011;Lee et al 2012Lee et al , 2013Thomson et al 2014) and thus that this enzyme likely has a higher binding affinity for bent DNA, such as at the apices of plectonemes in supercoiled DNA. To date, however, the proposed models cannot fully explain the below-equilibrium simplification phenomenon, indicating that the models may only partially reflect the mechanistic basis of this intriguing effect (Hardin et al 2011;Liu et al 2010;Martínez-García et al 2014;Seol et al 2013b;Thomson et al 2014;Yan et al 1999). Recently, it was demonstrated that the binding affinity of Topo IV is linearly related to the linking number for negatively supercoiled plasmid DNA (Litwin et al 2015), which is consistent with previous observations of Topo IIA binding to DNA crossovers (Zechiedrich and Osheroff 1990).…”
Section: Dna Twist (Torsion)-dependent Protein Activitysupporting
confidence: 69%
“…Structural studies and direct mechanical measurements have revealed that Topo IIA enzymes bend DNA upon binding (Dong and Berger 2007; Hardin et al 2011; Lee et al 2013; Lee et al 2012; Thomson et al 2014), thus Topo IIA likely has a higher binding affinity for bent DNA such as at the apices of plectonemes in supercoiled DNA. To date, however, the proposed models cannot fully explain the below-equilibrium simplification phenomenon, indicating that the models may only partially reflect the mechanistic basis of this intriguing effect (Hardin et al 2011; Liu et al 2010; Martínez-García et al 2014; Seol et al 2013b; Thomson et al 2014; Yan et al 1999). Recently, it was demonstrated that Topo IV binding affinity is linearly related to linking number for negatively supercoiled plasmid DNA (Litwin et al 2015), consistent with previous observations of Topo IIA binding to DNA crossovers (Zechiedrich and Osheroff 1990).…”
Section: Dna Writhe Dependent Protein Activitymentioning
confidence: 99%